A comprehensive review and update on the biologic treatment of adult noninfectious uveitis: part II. (November 2014) - Lee, Kyungmin; Bajwa, Asima; Freitas-Neto, Clovis A; Metzinger, Jamie Lynne; Wentworth, Bailey A; Foster, C Stephen
<x xml:space="preserve">Abstract</x> Introduction: Treatment of adult, noninfectious uveitis remains a major challenge for ophthalmologists around the world, especially in regard to recalcitrant cases. It is reported to comprise approximately 10% of preventable blindness in the USA. The cause of uveitis can be idiopathic or associated with infectious and systemic disorders. The era of biologic medical therapies provides new options for patients with otherwise treatment-resistant inflammatory eye disease. Areas covered: This two-part review gives a comprehensive overview of the existing medical treatment options for patients with adult, noninfectious uveitis, as well as important advances for the treatment ocular inflammation. Part I covers classic immunomodulation and latest information on corticosteroid therapy. In part II, emerging therapies are discussed, including biologic response modifiers, experimental treatments and ongoing clinical studies for uveitis. Expert opinion: The hazard of chronic corticosteroid use in the treatment of adult, noninfectious uveitis is well documented. Corticosteroid-sparing therapies, which offer a very favorable risk–benefit profile when administered properly, should be substituted. Although nothing is currently approved for on-label use in this indication, many therapies, through either translation or novel basic science research, have the potential to fill the currently exposed gaps.